Surge Capacity and Capability. A Review of the History and Where the Science is Today Regarding Surge Capacity during a Mass Casualty Disaster - Kearns, Randy D.; Cairns, Bruce A.; Cairns, Charles B. (Frontiers in Public Health, 2014)
Disasters which include countless killed and many more injured, have occurred throughout recorded history. Many of the same reports of disaster also include numerous accounts of individuals attempting to rescue those in great peril and render aid to the injured and infirmed. The purpose of this paper is to briefly discuss the transition through several periods of time with managing a surge of many patients. This review will focus on the triggering event, injury and illness, location where the care is provided and specifically discuss where the science is today.